Studi Deskriptif Mengenai Pengetahuan Ibu tentang Efek Samping Penggunaan Kontrasepsi Suntik 3 Bulan di TPMB Mutiara Kasih - Nur Nilam Sari; Tetti Surianti; Eka Wulansari; Lisna Lisna (Journal Research of Nursing & Midwifery (JRNM), 2025)
This progestin injectable contraceptive is a method used to prevent pregnancy in women through intramuscular injections that are effective for three months and do not require daily use. This contraceptive contains the hormone progesterone and does not interfere with breast milk production, making it safe for breastfeeding mothers. In addition to being practical, this method also has a high level of effectiveness in preventing pregnancy. However, like any contraceptive method, the 3-month injection also has side effects that need to be well understood by users to make informed decisions. This study was conducted to describe the level of maternal knowledge regarding the side effects of the 3-month injectable contraceptive at TPMB Mutiara Kasih. The research method used was a descriptive method with a qualitative approach through direct interviews with respondents. The results of the study showed that most mothers had limited knowledge about the side effects of the 3-month injectable contraceptive, such as menstrual irregularities, weight gain, mood changes, and reactions at the injection site. From the research findings, it can be concluded that knowledge is an important aspect that can increase awareness and readiness among mothers to deal with possible side effects of the 3-month injectable contraceptive. The lack of knowledge is likely due to the limited information provided by healthcare workers or the lack of access to other reliable sources. Therefore, regular education and counseling are urgently needed to improve mothers' understanding of the use and side effects of this contraceptive method.